Efficacy of Electrical Spinal Cord Stimulation with Neuromodulating Medications: A Systematic Review - Nadherny, Weston Case (Psychopharmacol Bull, 2020)
BACKGROUND: Chronic pain is a prevalent and debilitating problem for millions of people and spinal cord stimulation (SCS) is one option for treatment. It has been shown to have membrane stabilizing properties and is often used in conjunction with medications that are also believed to offer pain control through membrane stabilization. OBJECTIVE: The goal of this review is to analyze the effects of SCS combined with medications to evaluate for augmentative therapeutic effect. SETTING: Systematic review. METHODS: A systematic computerized search of the literature was conducted using PubMed, the Cochrane Library, and EMBASE for articles published in English. RESULTS: We report three articles that discuss the potential for augmentative effects of medication in combination with SCS. Located articles related primarily to SCS combined with Gabapentin, TCA, or SNRI. LIMITATIONS: The limited number of articles reflects a need for more investigation in this area. CONCLUSION: Based on the suspected mechanisms for SCS and neuromodulating medications, there is reason to believe adding these medical therapies may enhance the effects of SCS.